A facile approach to thermomechanically enhanced fatty acid-containing bioplastics using metal–ligand coordination. Issue 48 (20th November 2019) - Lamm, Meghan E.; Song, Lingzhi; Wang, Zhongkai; Lamm, Benjamin; Fu, Lin; Tang, Chuanbing
Abstract : Dynamic metal–ligand coordination creates physical crosslinking and thus improves chain entanglements for enhancing the thermomechanical properties of biobased polymers. Abstract : Biomass-based polymers show promise for the mitigation of environmental issues associated with petroleum-derived commodity polymers; however, due to poor entanglement, many of these polymers typically lack mechanical strength and toughness. Herein, we report a facile approach to utilizing metal–ligand coordination to create physical crosslinking, and thus chain entanglements for plant oil-derived polymers. A series of soybean oil-derived copolymers containing a pendant acid group can be easily synthesized using free radical polymerization. The resulting chain architecture can be controlled through supramolecular interactions to produce bioplastics with enhanced thermomechanical properties. The metal–ligand coordination in this work can be varied by changing the metal lability and the density of metal–ligand bonds, allowing for further control of properties. The final bioplastics remain reprocessable and feature good thermoplastic and stimuli-responsive properties.